Essentials of production and operations management - Wild, Ray. (London ; New York, NY : Cassell, 1990)
The book deals with the types of problems which would be encountered in establishing, designing, planning, running and maintaining a production or operating system. This edition had been updated to include new materials on operations policy, cost control and project management.
Includes indexes.
oif 15/10/14
Loan
Keywords: Production management; Industrial management